BIBLIOMETRIC ANALYSIS OF RESEARCH DEVELOPMENT ON PEDAGOGICAL CONTENT KNOWLEDGE (PCK) STUDIES IN THE FIELD OF EDUCATION BASED ON SCOPUS DATA (2014-2023) - Yuliani, Lulu; Hufad, Achmad; Komar, Oong; Robandi, Babang; Laksono, Bayu adi; Novitasari, Nastiti (Universitas Tanjungpura, 2025)
Pedagogical Content Knowledge (PCK) is an important educational conceptual framework. Researchers and educational practitioners work together to create Pedagogical Content Knowledge studies. Researchers and educators collaborate to gain a deeper knowledge of PCK and how to use it in real-world circumstances in the classroom through research and field experiences. The current analysis included research progress on PCK aspects from 2014 to 2023, namely the progress in the number of global publications on PCK aspects in the Scopus database from 2014 to 2023, the core journals of international publications in the field of PCK studies, the productivity of researchers in the field of PCK studies, the number of which originates from collaboration in international publications on PCK aspects of study, the development of international research publications, and the development of international research publications. The global publication Scopus instrumentation view database was used in this investigation. Data collected from Scopus was based on the terms instrumentation, instruments, measurements, medical instrumentation, virtual instrumentation, instrumentation system article title, abstract, and keywords of 2014-2023. The data comprised the number of years, daily posts of instrumentation features, author, and author's origin. Microsoft Excel was used to evaluate the data points. The VosViewer program was used to track the progress of worldwide publications on instrumentation issues. According to the results and discussion of growth developments in the field of pedagogical content knowledge studies indexed by Scopus from 2014 to 2022, the maximum number of publications (17.75%) occurred in 2022. The map of the development of the pedagogical content knowledge field based on co-words was classified into 6 clusters